Sunflower cake in diets for beef cattle: digestibility, kinetics and in vitro ruminal fermentation parameters (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to evaluate the effect of the inclusion of sunflower cake replacing soybean meal in beef cattle diets on the in vitro digestibility of dry matter (IVDDM), organic matter (IVDOM), crude protein (IVDCP) and the ruminal fermentation kinetics and parameters. The experiment was analyzed according to a completely randomized design. The treatments consisted of four levels of sunflower cake, 0, 200, 400, 600 g kg-1, replacing soybean meal in the concentrate of beef cattle diets. The coefficients of IVDDM, IVDOM and IVDCP presented a quadratic effect with the addition of sunflower cake. The soluble fraction (fraction B) degradation rate and total gas production decreased linearly with the inclusion of sunflower cake. Values of pH in ruminal fluid were higher for levels 0, 200 and 600 g kg-1 sunflower cake. Sunflower cake can replace soybean meal by up to 280 g kg-1 in the concentrate of beef cattle diets, improving the in vitro digestibility of dry matter organic, matter and crude protein. Levels above 400 g kg-1 reduce ruminal digestion rate, digestibility and release of final fermentation products.